Molecular characterisation of the first New Delhi metallo-β-lactamase 1-producing Acinetobacter baumannii from Tanzania. (27th January 2021) - Moyo, Sabrina J; Manyahi, Joel; Hubbard, Alasdair T M; Byrne, Rachel L; Masoud, Nahya Salim; Aboud, Said; Manji, Karim; Blomberg, Bjørn; Langeland, Nina; Roberts, Adam P
Abstract: Background: We aimed to characterise the genetic determinants and context of two meropenem-resistant clinical isolates of Acinetobacter baumannii isolated from children hospitalised with bloodstream infections in Dar es Salaam, Tanzania. Methods: Antimicrobial susceptibility was determined by disc diffusion E-test and broth microdilution. Genomes were completed using a hybrid assembly of Illumina and Oxford Nanopore Technologies sequencing reads and characterisation of the genetic context of resistance genes, multi-locus sequence types (STs) and phylogenetic analysis was determined bioinformatically. Results: Twelve A. baumannii were isolated from 2226 blood cultures, two of which were meropenem-resistant. The two meropenem-resistant isolates, belonging to distinct STs, ST374 and ST239, were found to harbour bla NDM-1, which was chromosomally located in isolate DT0544 and plasmid-located in isolate DT01139. The genetic environment of bla NDM-1 shows the association of insertion sequence ISAba 125 with bla NDM-1 in both isolates. Both isolates also harboured genes conferring resistance to other β-lactams, aminoglycosides and cotrimoxazole. Conclusions: This is the first report of New Delhi metallo-β-lactamase-producing isolates of A. baumannii from Tanzania. The genetic context of bla NDM-1 provides further evidence of the importance of ISAba 125 in the spread of bla NDM-1 in A. baumannii . Local surveillance should be strengthened to keep clinicians updated on the incidence of these and other multidrug-resistant and difficult-to-treat bacteria.